Enhancing Solar Absorption with Double-Layered Nickel Coatings and WS2 Nanoparticles on Copper Substrates - Susana Devesa; Zohra Benzarti; Gabriel Santos; Diogo Cavaleiro; António Cunha; João Santos; Sandra Carvalho (Energies, 2024)
This study focused on the development and characterization of multi-layered nickel coatings doped with WS2 nanoparticles and electrodeposited on copper substrates. To enhance the solar collector’s performance by improving the solar radiation conversion into heat, two distinct undercoatings were evaluated, along with the incorporation of WS2 nanoparticles in the black nickel layer. X-ray diffraction (XRD) analysis revealed that the bright and dull nickel undercoatings consisted of metallic nickel, whereas the black coatings comprised amorphous nickel oxide, inferred to be Ni2O3 based on energy-dispersive X-ray spectroscopy (EDS) analysis. Scanning electron microscopy (SEM) analysis of the undercoatings and black nickel morphology showed a compact surface with a relatively homogenous microstructure composed of polyhedric grains, which was free of visible cracks or pinholes. The undercoating influenced the brightness, the reflectivity and the reflectance of the black nickel films, with the dull undercoated sample showing the most promising results, with a total absorbance of 0.94. The incorporation of WS2 nanoparticles induced the formation of cracks and increased the porosity of the black nickel film. With an appropriate content of WS2 nanoparticles and the use of a dull undercoat, these drawbacks can be avoided. Concerning the integration of WS2 nanoparticles, a minor decrease in the brightness of the black films and a subsequent increase in the total absorbance ultimately led to an enhancement of the conversion of solar energy into thermal energy.